What We Really can Learn From Aviation: Checklist-based Team Time-Out in Conjunction With Interpersonal Competence Training for the Daily Management of a Surgical Department. (October 2021) - Hirche, Christoph; Kneser, Ulrich
Objective. Aviation and affiliated training concepts have gained a pioneering role in the establishment of interpersonal competence training for physicians and in particular for surgical disciplines. Strengthening interpersonal competence in conjunction with standardized processes and tools aims at implementing safety and error culture in the clinical surroundings while improving patient safety. In a surgical center, safety culture starts with decisive day-to-day management, continues with WHO team time-out and optimal surroundings for the operation, and goes beyond mortality and morbidity conferences and reevaluation of the daily work. Nevertheless, operational day-to-day management has been only little in the focus of security and error culture in surgical literature yet. Method. Interpersonal competence training has been introduced in the hospital group. In 2017, a checklist-based team time-out was implemented to optimize day-to-day management so that conflicts and collisions can be identified timely. Results. The daily completed checklist addresses changes in staff and resource availability, patient-relevant, and other organizational factors. The introduction has provided a significant level of stability and proven itself as part of the safety culture and exemplary leadership beyond the "classical" fields in surgery. Conclusion. This "simple" instrument from the aviation toolbox in conjunction with interpersonal competence training can be recommended to improve the management and safety culture in a surgical clinic to streamline operations and positively affect patient safety and staff development as well as employee satisfaction. Nevertheless, it is not sufficient to implement standard operation procedures templates and checklists, and they have to be lived daily and by everyone.